KHẢO SÁT HIỆU QUẢ CỦA CHẾ PHẨM PROBIOTIC ENTEROCOCCUS FAECIUM L3 TRÊN NGƯỜI TÌNH NGUYỆN KHỎE MẠNH - Ngô, Thanh Nam; Bùi, Thị Lan Anh; Phạm, Ngọc An; E.I., Ermolenko; N.A., Suvorov (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
EVALUATING EFFECTIVENESS OF PROBIOTICS BASED ON STREPTOCOCCUS FAECIUM L3 IN HEALTHY VOLUNTEERSThe results showed that usage of this probiotic can lead to decrease of white blood cells, lymphocytes, neutrophils contents in blood, to decline of serumglutamicoxaloacetic transaminase (GOT) and glutamic pyruvic transaminase (GPT) concentrations, not to demonstrate effects on serumal lipid profile. The number of participants with low concentrations of beneficial bacteria Lactobacillus spp. and Bifidobacterium spp. and the amount possessing opportunistic bacteria E. faecalis, S. aureus and Klebsiella spp. decreased. It is suggested that probiotics of E. faecium L3 has anti-inflamatory effects and improve balance of gut microbiota, without causing statistically significant changes in lipid metabolism.